“Are we saying every time you drink, you’ll get cancer?” Lessons learned from a focus group study of communicating difficult-to-swallow health-risk information - Ma, Zexin; Hintz, Elizabeth A.; Cassano, Bia (Frontiers in Communication, 2024)
This essay explores lessons learned when conducting focus group interviews with participants exposed to novel health-risk messages. Focus group participants exposed to new health-risk information might be defensive, affecting the quality of the data collected. Hence, accounting for potential participant defensiveness is of great importance for researchers who are developing and testing these health-risk messages. In this essay, I identify two forms of defensiveness that emerged in my focus group study evaluating cancer warning labels on alcoholic beverages: (1) actively counterarguing the health-risk message and (2) repeatedly modifying the health-risk message. I also offer four “lessons learned” to improve health-risk message testing in qualitative research practice: (a) communicate with empathy, (b) use personal stories, (c) forewarn participants, and (d) offer a self-affirmation opportunity. Overall, this essay contributes to the development of a typology of defensive strategies that focus group participants may use when exposed to novel health-risk messages. Additionally, it provides a methodological framework for guarding the integrity of the data and climate of the focus groups. These insights are valuable for health communication researchers and practitioners interested in conducting focus groups to assess health-risk messages.